Groups and Isomorphism
- The operation is associative so that \((ab)c = a(bc), \forall a,b,c \in G\)
- There exists an identity element. \(\exists e \in G\) such that \(ae = a = ea \forall a \in G\).
- Every element has an inverse. \(\forall a \in G, \exists a^{-1} \in G\) such that \(aa^{-1} = e = a^{-1}a\).
In addition to groups, we also have
- Monoids which satisfy \((1)\) and \((2)\).
- Semi-groups which satisfy \((1)\).
- Magma \(G, \cdot\) with no additional properties.
Basic Properties of Groups
In the next few propositions, we’ll prove that the identity element in a group is unique and similarly the inverses are unique.
Proof
Let \(e\) and \(e'\) be identity elements. Then by definition for any \(x, y \in G\)
If we let \(x = e'\) and let \(y = e\), then
From this we see that \(e = e'\) as desired. \(\ \blacksquare\)
Proof
Let \(a \in G\) and suppose for the sake of contradiction that \(a\) has two inverses \(b\) and \(c\). That is \(ab = e = ba\) and \(ac = e = ca\). Then,
Therefore, \(c = b\) which is a contradiction so the inverse must be unique. \(\ \blacksquare\)
By definition, \(b\) an inverse of \(a\) if \(ab = ba = e\) so it’s an inverse on both sides. This proposition proposes that checking only one side is enough. That is if \(ab = e\), then \(a = b^{-1}\) and \(b\) is the inverse. So what we want to show here is that given \(ba = e\), then \(b\) is the inverse of \(a\). We don’t check the other side. One side is enough to imply the other.
Proof
We know from the previous proposition that \(a\) has an inverse \(a^{-1} \in G\). Now consider the expression \(a^{-1}ab\). By associativity, we can reduce this expression in two ways
The left hand side
The right hand side is
So \(b = a^{-1}\) and therefore, \(ba = a^{-1}a = e\).
Proof (Book)
Suppose \(hg = e\), then
Suppose now that \(gh = e\), then
Proof
We know \(gg^{-1} = e\). By (2.1.2) \(g = (g^{-1})^{-1}\). \(\ \blacksquare\)
Proof
Notice that \((ab)(b^{-1}a^{-1}) = a(b((b^{-1}a^{-1})) = a((bb^{-1})a^{-1}) = a(ea^{-1}) = aa^{-1} = e\). Therefore, \((ab)^{-1} = b^{-1}a^{-1}\).
The Left and Right Multiplication Maps
The map \(L_a: G \rightarrow G\) defined by \(L_a(x) = ax\) is a bijection. Similarly,
the map \(R_a: G \rightarrow G\) defined by \(R_a(x) = xa\) is a bijection.
Proof
To show that the map \(L_a\) is a bijection, we need to show that \(L_a\) is both one to one and onto or equivalently that \(L_a\) has an inverse. We claim that the left multiplication by \(a^{-1}\) or \(L_{a^{-1}}\) is the inverse of \(L_a\). To see that,
Similarly,
So \(L_{a^{-1}}\) and \(L_a\) are inverse maps so both are bijective. \(\ \blacksquare\)
Proof
For \(ax = b\) to have a solution. The map \(L_a\) needs to be onto or surjective. For the solution to be unique, the map needs to be one to one or injective. Similarly for \(xa = b\) to have a solution, we want \(R_a\) to be a bijective. Since we proved earlier that \(L_a\) and \(R_a\) are bijections, then both equations have unique solutions. \(\ \blacksquare\)
Proof
Suppose \(ax = ay\). We know that \(L_a(x) = ax\) is one to one. So for any elements \(x, y \in G\), \(ax = ay\) must imply that \(x = y\) by definition of a one to one or injective map. A similar arguments shows that if \(xa = ya\) must imply that \(x = y\) by the injectivity of \(R_a\). \(\ \blacksquare\)
Proof (book)
A row in the multiplication table can be represented by a left multiplication map \(G \rightarrow G\) if you fix the element multiplied on the left. We know the left multiplication map is a bijection. Therefore every element/result must be unique and each element of \(G\) must show up in the row. Similarly, each column can be represented by a right multiplication map. The map is a bijection and so each element must be unique and shown exactly once. (TODO clean up this proof)
Associativity in Groups
We know by definition that the product is associative so for all \(a, b, c \in G\), we have \((ab)c = a(bc)\). What about the product of 4 or more elements? is it associative? For example, there are five ways to group four elements
\(a(b(cd))\) and \(((ab)c)d\) follow from the definition. For the rest, see that
How many ways are there to associate an \(n\)-fold product?
In general this works for any number of elements. Formally,
- The product of one element is that element \((a) = a\).
- The product of two elements agrees with the given operation \((ab) = ab\).
- For all \(n \geq 2\), for all \(a_1,...,a_n \in M\), and for all \(1 \leq k \leq n-1\), $$ \begin{align*} a_1a_2...a_n = (a_1...a_k)(a_{k-1}...a_n) \end{align*} $$
Proof
By induction on \(n\).
Base Case: For \(n \leq 3\), property \((c)\) holds by definition.
Inductive Case: Suppose this is true for all \(1 \leq r \leq n\) where a unique product of \(r\) elements satisfies the properties \((a)-(c)\) above. Suppose now that we have \(n\) elements. Fix elements \(a_1, ...,a_n \in M\). By the inductive hypothesis, the \(n-1\) products
are defined since we have at most \(n-1\) elements. … [TODO]
General Powers
Now, we turn into defining powers of an element in a group
- \(a^0 = e\).
- \(a^1 = a\).
- \(a^{-1} \) is the inverse of \(a\).
- \(n \geq 1\), \(a^{n+1} = a^n a\).
- \(n \leq -1\), \(a^{n-1} = a^n a^{-1}\).
Based on this definition we have the following proposition
Proof (1)
By induction on \(n\).
Base Case \((n = 1)\): \(a^m a = a^{m+1}\) by definition.
Inductive Case: Suppose the inductive hypothesis is true for \(n\). That is \(a^m a^n = a^{m+n}\). Now observe that
Proof (2)
By induction on \(n\).
Base Case \((n = 1)\): \((a^{m})^1 = a^{m}\).
Inductive Case: Suppose the inductive hypothesis is true for \(n\). That is \((a^m)^n = a^{mn}\). Now observe that
Isomorphism
One thing that we want to do is to compare two groups. For example take \((\mathbf{Z}_4, +)\), the symmetries of the rectangle, \((\phi(5), \cdot)\) and \((\phi(8), \cdot)\). These are all groups with exactly 4 elements. To compare two groups, we want to see if we can construct a bijection between the two groups. Formally, this is called an isomorphism as follows
The map \(\varphi\) is called an isomorphism.
We write \(H \approx G\) for \(G\) is isomorphic to \(H\).
An an example consider the group of symmetries of the equilateral triangle \(D_3\) and the group \(S_3\) (permutations of \(\{1,2,3\}\)). Both groups contain exactly 6 elements. They turn out to be isomorphic. Observe here that if we assign the vertices \(A\) to \(1\), \(B\) to \(2\) and \(C\) to \(3\), then the rotation \(a\) flips the vertices \(B\) and \(C\). This is exactly the same as the permutation \((2 \ 3)\). Similarly, if you think about the rotation \(r\), you’ll notice that \(r\) permutes the vertices in the exact way as the permutation \((1 \ 2 \ 3)\). In fact, all permutations. Another example is the \(b\) rotation. This rotation fixes \(b\) and rotates \(a\) and \(c\). This is also the same as the permutation \((1 \ 3)\). We can map the rest of the symmetries as follows
\(D_3\) | \(S_3\) |
\(id\) | \(id\) |
\(r\) | \((1 \quad 2 \quad 3)\) |
\(a\) | \((2 \quad 3)\) |
\(r^2\) | \((1 \quad 3 \quad 2)\) |
\(b\) | \((1 \quad 3)\) |
\(c\) | \((1 \quad 2)\) |
Proof
Let \(a', b' \in H\). We want to show that
Let \(a' = \varphi(a)\) and \(b' = \varphi(b)\) for some \(a, b \in G\). Since \(\varphi\) is injective then it suffices to show that
The right hand side is clearly just \(a'b'\). \(\varphi\) is an isomorphism so the left hand side becomes
Therefore \(\varphi^{-1}\) is an isomorphism as desired. \(\ \blacksquare\).
Groups of Small Order
The order of a group is the number of elements in it. Formally,
One interesting thing to do is to classify all groups of a given finite order. If we do that for small sizes, we get
- Order 0: None because we need to at least have the identity element.
- Order 1: \(G = \{e\}\). Other groups of order 1 can be \(G'=\{1\}\). These two groups are isomorphic. Technically, it's a different set but to us, they're the same group. So "up to isomorphism", there is only one group of size 1.
- Order 2: Up to isomorphism, the only unique group is \(\mathbf{Z}_2 = \{[0], [1], [2]\}\).
- Order 3: Up to isomorphism, the only unique group is \(\mathbf{Z}_3\). All other groups of size 3 will be isomorphic to \(\mathbf{Z}_3\).
- order 4: Up to isomorphism, there are two unique groups. \(\mathbf{Z}_4 \) and \(\mathbf{Z}_2 \times \mathbf{Z}_2\) (symmetries of the rectangle). Groups of order 4 can be isomorphic to either one.
- Order 5: Up to isomorphism, the only unique group is \(\mathbf{Z}_5\)
- Order 6: Up to isomorphism, we have two unique groups. \(\mathbf{Z}_6\) and \(S_3 \approx D_3\). These two groups are not isomorphic because \(S_3\) is non-abelian while \(\mathbf{Z}_6\) is abelian. The proof for this fact is next.
Proof (Lecture Notes)
Suppose that \(\phi: G \rightarrow H\) is an isomorphism. Furthermore, let \(a, b \in G\) and \(a', b' \in H\) such that \(\phi^{-1}(a') = a\) and \(\phi^{-1}(b') = b'\). We will prove both directions of the statement.
\(\Rightarrow\): Suppose that \(G\) is abelian. We will show that \(H\) is abelian. Observe that
But we know that \(G\) is abelian and so \(ab = ba\) so \(\phi(ab) = \phi(ba)\) and therefore we must have \(a'b' = b'a'\).
\(\Leftarrow\): Now suppose that \(H\) is abelian. Then,
We know that \(a'b' = b'a'\) because \(H\) is abelian. But since \(\phi\) is injective, this implies that \(ab = ba\). (remember injective means that \(f(a)=f(b) \implies a = b\)). \(\ \blacksquare\)
Note that for this direction, we could’ve instead relied on \(\phi^{-1}\) being an isomorphism itself. and so observe that
\(H\) is abelian so \(a'b' = b'a'\) so \(\phi^{-1}(a'b') = \phi^{-1}(b'a')\) and thus \(ab = ba\).
Extra Notes from the book: Two groups are isomorphic means that the multiplication tables match up. In fact, not only that but the identity elements and inverses of elements match up as well. The following propositions state these facts.
Proof
Since \(\phi\) is an isomorphism, then we know that for each \(h \in H\), there is a \(g \in G\) such that \(\phi(g) = h\). Therefore,
So \(\phi(e_G)\) is an identity element. But since the identity element is unique, then \(\phi(e_G) = \phi(e_H)\).
To show that \(\phi(g^{-1}) = \phi(g)^{-1}\), see that
So \(\phi(g)\) is the inverse of \(\phi(g^{-1})\) or in other words \(\phi(g)^{-1} = \phi(g^{-1})\) as we wanted to show. \(\ \blacksquare\)
References
- MATH417 by Charles Rezk
- Algebra: Abstract and Concrete by Frederick M. Goodman